2011
DOI: 10.1038/jid.2011.211
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Restores C-Fiber Function and Prevents Pressure Ulcer Formation in Diabetic Mice

Abstract: Pressure-induced vasodilatation (PIV), a cutaneous physiological neurovascular (C-fiber/endothelium) mechanism, is altered in diabetes and could possibly contribute to pressure ulcer development. We wanted to determine whether recombinant human erythropoietin (rhEPO), which has protective neurovascular effects, could prevent PIV alteration and pressure ulcer formation. We developed a skin pressure ulcer model in mice by applying two magnetic plates to the dorsal skin. This induced significant stage 2 ulcers (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…However, models that utilize application of compressive load to skin to study development of DTI are very scarce. Current animal models include use of magnetic devices [15], [66] or spinal cord injury models [67]. Although important knowledge was gained from these studies, the correlation to human condition is limited, mostly because of anatomical difference between rodents and humans and limitations in precise control of the applied load/pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, models that utilize application of compressive load to skin to study development of DTI are very scarce. Current animal models include use of magnetic devices [15], [66] or spinal cord injury models [67]. Although important knowledge was gained from these studies, the correlation to human condition is limited, mostly because of anatomical difference between rodents and humans and limitations in precise control of the applied load/pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that repeated cycles of ischemia reperfusion, impairing blood and lymph flow locally, lead to cell necrosis in the epidermis, dermis, subcutaneous adipose, and skeletal muscle tissues [10][11][12]. Prior preclinical pressure ulcer studies have used a variety of rodent models including the diabetic mouse [13][14][15][16][17][18][19], and only two murine studies have examined the effect of age on healing outcomes [16,20]. In one study, chitosan scaffolds with or without fibroblast growth factor 2 were found to accelerate the closure of pressure ulcer wounds in old (20)(21)(22) months old [mo]) mice [16].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are some animal models of chronic wounds [38][41]. However, these animal models employed two magnetic plates to dorsal skin for making PUs [38], [39] or treated with drugs to induce diabetic conditions before making full thickness wound [40], [41] to create the chronic wounds, therefore cannot be used for assessing the effect of pressure applied to the existing wounds on its healing process.…”
Section: Discussionmentioning
confidence: 99%